DODOGERAN DANCE LEARNING - Dhea Muthia; Heny Rohayani; Agus Budiman (Universitas Pendidikan Indonesia, 2022)
This research is about learning planning, the learning process and the evaluation of learning the Dodogeran Dance which has agile, cheerful, and funny movements, so that this dance can be performed in general by participants studying SD-SMA at the Sinar Seli Asih Studio, Bekasi City. The purpose of writing this article is to describe how to plan the learning of Dodogeran Dance at the Sinar Seli Asih Studio, to describe the learning process of Dodogeran Dance at the Sinar Seli Asih Studio, and to describe the evaluation of learning the Sinar Seli Asih Dodogeran Dance in Bekasi City. This qualitative research uses descriptive analysis method.The participants in this study were Eem Biliyanti as the creator and trainer of the Dodogeran Dance, Sukarsa as the leader of the Sinar Seli Asih Studio and the participants in the study of the Sinar Seli Asih Studio.The technique used in data collection is observation, interview, documentation, and literature study. The learning process for the Dodogeran dance material is approximately six months, after which a studio evaluation is held every six months. The learning methods used in the Sinar Seli Asih Studio are lecture, demonstration, imitative (imitation), and drill (practice) methods. The trainer provides an explanation of the material to be delivered orally, after that provides the basic techniques, participants learn to imitate the movements made by the trainer, then participants learn to do exercises continuously. The results of the research obtained in learning the Dodogeran dance are learning plans at the Sinar Seli Asih Studio, which are not written as in the case of lesson plans